Leaders’ After-hours Electronic Communication Expectations and Employees’ Knowledge Management - Li, Runyao (International Journal of Global Economics and Management, 2024)
Actively meeting the expectations of leaders to be “in touch” and “responsive” during off-hours is a new type of workplace survival rule for employees in the era of the digital economy. The study explores the “double-edged sword” effect of leaders’ after-hours electronic communication expectations (AECE) on subordinates’ knowledge management behaviors and the boundary conditions based on affective event theory from the view of emotions. This exploration utilizes both an experimental study and a multi-time point field study. The results indicate that for employees with a high level of perspective-taking competence, AECE stimulates deep acting, consequently enhancing employees’ knowledge-sharing behaviors. Conversely, for employee with low perspective-taking competence, AECE triggers surface acting, leading to an increase in knowledge-hiding behaviors. The findings provide a more comprehensive explanation of the differential impact of AECE on subordinates’ knowledge management behaviors, which enriches the existing literature on AECE, extends the application of affective event theory in the context of enterprises’ digital transformation, and provides insights for organizations to effectively implement and manage AECE in the evolving landscape of workplace dynamics, often referred to as the “new normal”.